Qifu Yixin Formula Improves Heart Failure by Enhancing β-Arrestin2 Mediated the SUMOylation of SERCA2a - Wang X; Yang J; Lu C; Hu Y; Xu Z; Wan Q; Zhang M; Shi T; Liu Z; Liu Y (Drug Design, Development and Therapy, 2024)
Xinting Wang,1,* Jiahui Yang,1,* Cheng Lu,2 Yinqin Hu,1 Zhaohui Xu,1 Qiqi Wan,1 Meng Zhang,1 Tianyun Shi,1 Zhirui Liu,1 Yongming Liu1 1Department of Cardiology, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, 200021, People’s Republic of China; 2Department of Cardiology, Seventh People’s Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, Shanghai, 200137, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yongming Liu, Department of Cardiology, Shuguang Hospital Affiliated to Shanghai University of Traditional Chinese Medicine, No. 185, Pu’an Road, Huangpu District, Shanghai, 200021, People’s Republic of China, Email liuyongming@foxmail.comPurpose: This study aimed to elucidate the protective mechanism of Traditional Chinese Medicine (TCM) Qifu Yixin formula (QFYXF) to improve heart failure (HF) by promoting β-arrestin2 (β-arr2)-mediated SERCA2a SUMOylation.Materials and Methods: The transverse aortic constriction (TAC)-induced HF mice were treated with QFYXF or carvedilol for 8 weeks. β-arr2-KO mice and their littermate wild-type (WT) mice were used as controls. Neonatal rat cardiomyocytes (NRCMs) were used in vitro. Cardiac function was evaluated by echocardiography and serum NT-proBNP. Myocardial hypertrophy and myocardial fibrosis were assessed by histological staining. β-arr2, SERCA2a, SUMO1, PLB and p-PLB expressions were detected by Western blotting, immunofluorescence and immunohistochemistry. SERCA2a SUMOylation was detected by Co-IP. The molecular docking method was used to predict the binding ability of the main active components of QFYXF to β-arr2, SERCA2a, and SUMO1, and the binding degree of SERCA2a to SUMO1 protein.Results: The HF model was constructed 8 weeks after TAC. QFYXF ameliorated cardiac function, inhibiting myocardial hypertrophy and fibrosis. QFYXF promoted SERCA2a expression and SERCA2a SUMOylation. Further investigation showed that QFYXF promoted β-arr2 expression, whereas Barbadin (β-arr2 inhibitor) or β-arr2-KO reduced SERCA2a SUMOylation and attenuated the protective effect of QFYXF improved HF. Molecular docking showed that the main active components of QFYXF had good binding activities with β-arr2, SERCA2a, and SUMO1, and SERCA2a had a high binding degree with SUMO1 protein.Conclusion: QFYXF improves HF by promoting β-arr2 mediated SERCA2a SUMOylation and increasing SERCA2a expression.Keywords: heart failure, Qifu Yixin Formula, β-arrestin2, SERCA2a, SUMOylation